Kurang Energi Kronis Berhubungan dengan Kejadian Anemia pada Ibu Hamil - Subriah, Subriah; Safitri, Inka Dewi; Umar, Syaniah; Saadong, Djuhadiah (Jurnal Kebidanan Malakbi, 2021)
KEK (Chronic Energy Deficiency) is a condition caused by an imbalance in nutritional intake, which lasts (chronic) while the anemia in pregnant women is closely related to the nutritional status of pregnant women because anemia is one sign that the mother suffers from malnutrition. This study aims to determine the relationship between chronic energy deficiency and anemia in pregnant women at the Public healthcanter Mangasa, Makassar City. The type of research used is an analytic survey with a cross-sectional design. The sampling technique was purposive sampling with 78 respondents. The results of the statistical test with the chi-square test are known as the significance value of p (0.005) <Î± (0.05), meaning that the p value is smaller than the value of Î± at 95% confidence level with 1 degree of freedom, it can be concluded that the null hypothesis is rejected and this accepted hypothesis means that there is a chronic lack of energy relationship with the incidence of anemia in pregnant women at the Public healthcenter Mangasa, Makassar City. Therefore, health workers are expected to be able to carry out continuous strengthening of KIE (communication, information, and education) in pregnant women with KEK risk and anemia to pay more attention to their health status from all factors in readiness to face pregnancy with a cross-sectoral approach.